(untitled) (Research, Society and Development, 2022)
Springs are important environmental systems for the maintenance of hydrological, geomorphological and biological balance. However, in urban areas, these springs have been intensely modified by human action. One of the main consequences of urban interventions on the dynamics of springs is changes in water quality. One of the main consequences of urban interventions on the dynamics of springs is changes in water quality. In addition, periods of greater precipitation can interfere with this dynamic. Therefore, the present study aimed to evaluate the water quality index - WQI at the source of the Sussuapara stream in the municipality of Palmas-TO in the year 2021. Nine parameters were studied to assess water quality; four samples were collected in the dry months and four in the rainy months. The results obtained were compared with Conama Resolution nº 357 and showed that the WQI of the headwaters of the Sussuapara stream in the dry months was higher than in the rainy months, being classified as “Good” and “Regular”, respectively. The results showed that the impacts caused by surface runoff and location of the spring are significant in the water quality index.